Gabon : First and Second Reviews of the Extended Arrangement under the Extended Fund Facility, Requests for Waivers for Nonobservance of Performance Criteria, Establishment of Performance Criteria, and Financing Assurances Review-Press Release; Staff Report; Staff Supplement; and Statement by the Executive Director. (IMF Staff Country Reports; Country Report ;, 2022)
On July 28, 2021, the IMF Executive Board approved a 36-month extended arrangement under the Extended Fund Facility (EFF) with a total access of SDR 388.8 million (180 percent of quota) to help Gabon respond to the economic fallout from the COVID-19 pandemic and support the authorities' economic and financial reform program. A nascent economic recovery is underway, and the outlook is broadly positive but remains subject to considerable uncertainty and a range of risks. The war in Ukraine will affect the economy through various channels, including higher food and fuel prices.